2016
DOI: 10.1007/s10964-016-0607-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Vulnerabilities to Depression for Adolescents in Single-Mother and Two-Parent Families

Abstract: Although research consistently suggests that adolescents in single-mother families are at increased risk for depression, the mechanisms that explain this relationship are unclear. In a community sample of adolescents (N = 368; ages 12–16; 50% female; 50% White) and their mothers (42% single), adolescents completed measures of depressive symptoms, rumination, and depressogenic inferential style at baseline and two yearly follow-ups. Mothers reported on stressful events that occurred in the child’s life from bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…Another study in United States reported that adolescents living with single mothers were more likely to experience greater depressive symptoms than those with cohabitating mothers (β = 0.21, P < .001). 27 Adolescents from broken families had significantly higher levels of depression, with 25% of adolescents with divorced parents having moderate and severe depression. 28 Parental divorce affected psychological stability of their children more so during adolescence resulting in negative consequences especially regarding psychosocial impairment: lower self-esteem and the feeling of consternation, frequent depressive mood or more suicidal thoughts, and even more attempts of suicide.…”
Section: Discussionmentioning
confidence: 97%
“…Another study in United States reported that adolescents living with single mothers were more likely to experience greater depressive symptoms than those with cohabitating mothers (β = 0.21, P < .001). 27 Adolescents from broken families had significantly higher levels of depression, with 25% of adolescents with divorced parents having moderate and severe depression. 28 Parental divorce affected psychological stability of their children more so during adolescence resulting in negative consequences especially regarding psychosocial impairment: lower self-esteem and the feeling of consternation, frequent depressive mood or more suicidal thoughts, and even more attempts of suicide.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, negative parenting behaviors have been shown to be more common in single-mother households [12]. The increased risk for mental health problems in children of single-mother households has also been attributed to increased experience of stressful life events [13]. While these factors add to the total burden of risk, single motherhood stays significantly associated with youth psychopathology after controlling for poverty and maternal psychopathology [14].…”
Section: Introductionmentioning
confidence: 99%
“…Parental mental health problems, especially those of mothers, are also associated with an increased risk of adolescent depression [8,9]. Other predisposing factors for offspring's depression are shown to include: single-parenthood, parental low education or unemployment and childhood sexual abuse [10][11][12][13][14][15]. Researchers have described four possible mechanisms for a parent's depression contributing to the onset of depression in their offspring: (1) genetic heritability, (2) innate dysfunctional neuro-regulatory mechanisms on the child, (3) child exposure to negative parenting patterns, and (4) stressful circumstances in a child's life [16].…”
Section: Effect Of Family Background In Depressionmentioning
confidence: 99%